Democrats’ mistakes and the birth of authoritarian rule: ramón s. castillo and the fall of conservative democracy in Argentina - Taccone, Nicolás (2023)
Fil: López, Ignacio Alejandro. Pontificia Universidad Católica Argentina. Facultad de Ciencias Sociales; Argentina